G-quadruplexes in the evolution of hepatitis B virus - Brázda, Václav; Dobrovolná, Michaela; Bohálová, Natália; Mergny, Jean-Louis (Nucleic acids research, 2023)
Hepatitis B virus (HBV) is one of the most dangerous human pathogenic viruses found in all corners of the world. Recent sequencing of ancient HBV viruses revealed that these viruses have accompanied humanity for several millenia. As G-quadruplexes are considered to be potential therapeutic targets in virology, we examined G-quadruplex-forming sequences (PQS) in modern and ancient HBV genomes. Our analyses showed the presence of PQS in all 232 tested HBV genomes, with a total number of 1258 motifs and an average frequency of 1.69 PQS per kbp. Notably, the PQS with the highest G4Hunter score in the reference genome is the most highly conserved. Interestingly, the density of PQS motifs is lower in ancient HBV genomes than in their modern counterparts (1.5 and 1.9/kb, respectively). This modern frequency of 1.90 is very close to the PQS frequency of the human genome (1.93) using identical parameters. This indicates that the PQS content in HBV increased over time to become closer to the PQS frequency in the human genome. No statistically significant differences were found between PQS densities in HBV lineages found in different continents. These results, which constitute the first paleogenomics analysis of G4 propensity, are in agreement with our hypothesis that, for viruses causing chronic infections, their PQS frequencies tend to converge evolutionarily with those of their hosts, as a kind of 'genetic camouflage' to both hijack host cell transcriptional regulatory systems and to avoid recognition as foreign material.
Keywords: virus hepatitidy B; Hepatitis B virus; Paleontology; paleontologie; Biological Evolution; Genomics; G-kvadruplexy; lidé; biologická evoluce; genom lidský; Humans; G-Quadruplexes; Genome, Human; genomika